2001
DOI: 10.1001/jama.286.18.2257
|View full text |Cite
|
Sign up to set email alerts
|

A Founder Mutation in Presenilin 1 Causing Early-Onset Alzheimer Disease in Unrelated Caribbean Hispanic Families

Abstract: The Gly206Ala mutation was found in 8 of 19 unrelated Caribbean Hispanic families with early-onset familial AD. This genetic change may be a prevalent cause of early-onset familial AD in the Caribbean Hispanic population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 42 publications
2
78
0
Order By: Relevance
“…APOE genotyping was carried out as previously described with slight modifications [29,30]. Genotyping for the PSEN1 Gly206Ala mutation, which we previously described as a founder mutation in this population, was performed as in Athan et al [31].…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…APOE genotyping was carried out as previously described with slight modifications [29,30]. Genotyping for the PSEN1 Gly206Ala mutation, which we previously described as a founder mutation in this population, was performed as in Athan et al [31].…”
Section: Genotypingmentioning
confidence: 99%
“…Because the marker at 14q32 yielded a significant LOD and is proximal to PSEN, we screened one affected person from each family for a PSEN1 mutation, Gly206Ala, specific to Caribbean Hispanics [31]. From the screen, we identified six individuals with this mutation who had an average age-at-onset of 57 years.…”
Section: Linkage Analysismentioning
confidence: 99%
“…Previously, we have shown that the study population is relatively homogeneous. 15 Overall, 237 individuals met the criteria for probable AD, 157 were unaffected. The study included families with affected sibpairs as well as families with multiple individuals with AD who were distantly related (eg, avunculars, cousins).…”
Section: Subjects and Familiesmentioning
confidence: 99%
“…12,13 To investigate the genetics of AD in this population, we initiated a linkage study. Our initial results included a strong association between APOE-e4 and late-onset familial AD, 14 a founder mutation in presenilin 1 (PSEN1 [MIM 104311]) among families with early-onset AD, 15 and modest evidence for linkage to chromosome 12p for late-onset AD in this population. 16 In this report, we describe the results of fine mapping on chromosomes 10q and 18q based on the results of the first genome scan for familial AD using families of Caribbean Hispanic descent.…”
mentioning
confidence: 99%
“…AD can be subdivided into sporadic type and familial type. The familial AD (FAD) is mostly early-onset, accounting for less than 5% of all AD cases, with Presenilin-1(PSEN1) and Presenilin-2 (PSEN2) as its genes, of which PSEN1 stands at the top [1][2][3][4]. Though, DLB is found mostly sporadic, without any confirmed genetic risk factor.…”
Section: Introductionmentioning
confidence: 99%